Comment l’extension de la communication bouleverse l’éthique et l’argumentation - Gilles Gauthier (Communication)
Communication trumps information as the regulator of social mediation. Journalism is no longer the sole moderator in the social debate and journalistic practices are less informative and more communicative. The extension of communication at the expense of information brings about two shifts. First, it dilutes ethics into moralism. Second, it equates argumentation with the simple expression of conviction. This double drift arose because communication and information have a different relationship to reality. Information proceeds from the principle of realism: it presupposes the pre-existence of the reality with which it is confronted. Communication proceeds from the principle of constructivism: it establishes a new reality.